Experiential Learning pada Kisah Nabi Musa dan Nabi Khidr dalam Q.S Al-Kahfi Ayat 62-82 - Yulianti, Ferina; Muslih, Hafid; Karman, Karman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Experiential learning in educational research studies has proven effective in improving students' academic performance. Therefore, it is important to check the Al-Quran for any verses that might be applicable in this situation. In Q.S. Al-Kahf [18]: 62–82, the narrative of Prophet Musa and Prophet Khidr is an example of experiential learning that will be examined in this study. The strategy is a qualitative strategy. This kind of investigation is done at libraries. The Al-Qur'an and books of interpretation served as primary data sources for this study's literature review, while articles from journals served as secondary data sources. At the same time, the maudhu'i interpretation approach is the one that is employed. The findings indicated that Prophet Musa's learning while he studied under Prophet Khidr implied several levels of experience-based learning, including: 1) the real experience stage, namely when Prophet Musa was directly involved in demonstrations conducted by Prophet Khidr; 2) the reflection observation stage, namely when Prophet Musa observed a series of events shown by Prophet Khidr from a sharia perspective; 3) the conceptualization stage, namely when the Prophet Khidr explained his actions during their journey; and 4) the implementation or experiment stage which is implicitly known from the process of training and habituation of patience carried out by Prophet Musa during his journey with Prophet Khidr.